Sleep Timing, Stability, and BP in the Sueño Ancillary Study of the Hispanic Community Health Study/Study of Latinos - Abbott, Sabra M; Weng, Jia; Reid, Kathryn J; Daviglus, Martha L; Gallo, Linda C; Loredo, Jose S; Nyenhuis, Sharmilee M; Ramos, Alberto R; Shah, Neomi A; Sotres-Alvarez, Daniela; Patel, Sanjay R; Zee, Phyllis C (Chest, 2019)
Timing and stability of the sleep-wake cycle are potential modifiable risk factors for cardiometabolic disease. The aim of this study was to evaluate the relationship between objective measures of sleep-wake timing and stability with cardiometabolic disease risk. In this multicenter, cross-sectional, population-based study, actigraphy data were obtained from the 2,156 adults, aged 18 to 64 years, recruited from the Sueño ancillary study of the Hispanic Community Health Study/Study of Latinos (2010-2013). These data were correlated with measures of cardiometabolic disease risk, including systolic and diastolic BPs, homeostatic assessment of insulin resistance, glycosylated hemoglobin, BMI, and hypertension and diabetes status. Each 10% decrease in interdaily stability was associated with a 3.0% absolute increase in the prevalence of hypertension (95% CI, 0.6-5.3; P < .05), an increase in systolic BP by 0.78 mm Hg (95% CI, 0.12-1.45; P < .05) and an increase in diastolic BP by 0.80 mm Hg (95% CI, 0.28-1.32; P < .05). In addition, delaying the midpoint of sleep by 1 h was associated with an increase in systolic BP by 0.73 mm Hg (95% CI, 0.30-1.16; P < .01) and diastolic BP by 0.53 mm Hg (95% CI, 0.17-0.90; P < .01). These associations were not significant after adjusting for shift work status. No association was found between interdaily stability or sleep timing and diabetes, BMI, or insulin resistance. These results suggest that beyond sleep duration, the timing and regularity of sleep-wake schedules are related to hypertension prevalence and BP.